Spatial Differentiation of Ecological Environment Quality and the Influencing Factors in Cities Within the Beijing–Tianjin–Hebei Region Based on LCZ and RSEI - Chaoguang Zhang; Zheng Wang; Jinze Wang; Xiaoying Ding; Yifei Peng (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
The ecological environment is crucial for human health and sustainable development. As urbanization and urban expansion have a significant impact on ecological environment quality, it is necessary to incorporate indicators that characterize urban morphological features into the ecological environment quality evaluations. This study combines the remote sensing ecological index (RSEI) with the local climate zone (LCZ) scheme to evaluate the ecological quality of urban environments and analyze spatial heterogeneity across cities in the Beijing-Tianjin-Hebei region. The results reveal that the same LCZ categories exhibit similar RSEI characteristics across different cities, validating the effectiveness of the LCZ scheme in assessing urban ecological quality. Among them, sparsely built and open low-rise types consistently show higher ecological quality, whereas compact high-rise and heavy industrial types are associated with lower RSEI values. In terms of the influencing factors, land cover indicators—particularly the normalized difference built-up index, tree height, and pervious surface fraction—emerge as dominant drivers. Urban morphological, climatic, and socioeconomic factors also influenced specific LCZ categories in certain cities. The findings underscore the importance of integrating ecological considerations into urban planning, particularly in highly urbanized and industrialized areas. Strategies should focus on increasing vegetation cover, optimizing building density, and mitigating the adverse effects of urban expansion and industrialization to improve urban ecological quality.